2021
DOI: 10.1161/strokeaha.120.033040
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 Inhibitors Plus Aspirin Versus Aspirin Alone in Patients With Minor Stroke or High-Risk Transient Ischemic Attack

Abstract: Background and purpose: We performed a systemic review and meta-analysis to elucidate the effectiveness and safety of dual antiplatelet (DAPT) therapy with P2Y12 inhibitors (clopidogrel/ticagrelor) and aspirin versus aspirin monotherapy in patients with mild ischemic stroke or high-risk transient ischemic attack. Methods: Following Preferred Reported Items for Systematic Review and Meta-Analysis standards for meta-analyses, Medline, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…and Death (THALES) trial(109)(110)(111)(112). The ongoing Clopidogrel with Aspirin in High-risk patients with Acute Non-disabling Cerebrovascular Events II (CHANCE-2, NCT04078737) trial is evaluating the superiority of the Ticagrelor-Aspirin combination over Clopidogrel-Aspirin therapy in CYP2C19 loss of function carriers with minor stroke or transient ischemic attack (TIA)(113).AnticoagulationTheNew Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial vs. ASA [Acetylsalicylic Acid] to Prevent Embolism in Embolic Stroke of Undetermined Source (NAVIGATE-ESUS) and the Randomized Double-Blind Evaluation in Secondary Stroke Prevention Comparing The Efficacy Of Oral Thrombin Inhibitor Dabigatran Etexilate for Secondary Stroke Prevention in Patients With Embolic Stroke of Undetermined Source (RE-SPECT-ESUS) trials have shown that universal full-dose oral anticoagulation is not an effective strategy to reduce the risk of stroke recurrence in patients with ESUS(5,6).…”
mentioning
confidence: 99%
“…and Death (THALES) trial(109)(110)(111)(112). The ongoing Clopidogrel with Aspirin in High-risk patients with Acute Non-disabling Cerebrovascular Events II (CHANCE-2, NCT04078737) trial is evaluating the superiority of the Ticagrelor-Aspirin combination over Clopidogrel-Aspirin therapy in CYP2C19 loss of function carriers with minor stroke or transient ischemic attack (TIA)(113).AnticoagulationTheNew Approach Rivaroxaban Inhibition of Factor Xa in a Global Trial vs. ASA [Acetylsalicylic Acid] to Prevent Embolism in Embolic Stroke of Undetermined Source (NAVIGATE-ESUS) and the Randomized Double-Blind Evaluation in Secondary Stroke Prevention Comparing The Efficacy Of Oral Thrombin Inhibitor Dabigatran Etexilate for Secondary Stroke Prevention in Patients With Embolic Stroke of Undetermined Source (RE-SPECT-ESUS) trials have shown that universal full-dose oral anticoagulation is not an effective strategy to reduce the risk of stroke recurrence in patients with ESUS(5,6).…”
mentioning
confidence: 99%
“…11 Dual antiplatelet therapy (DAPT) with aspirin and clopidogrel or ticagrelor is more effective than aspirin alone for the prevention of recurrent stroke. 12 A meta-analysis also concluded the effectiveness of DAPT however there is a higher risk of major bleeding which needs to be assessed during therapeutic strategies. 13 In a study conducted in Ottawa Hospital, Ontario , Canada there was however no statistical difference between clopidogrel and ticagrelor for the primary outcome of TIA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the slight variation in the definition of minor stroke between the CHANCE or POINT trial (NIHSS score 0–3) and the ARAMIS trial (NIHSS score 0–5), a meta-analysis has demonstrated the superiority of DAPT over aspirin monotherapy in patients with minor stroke or high-risk transient ischemic attack, irrespective of the NIHSS score for minor stroke. [ 16 ] The determination of the loading dose of antiplatelet drug is of utmost importance in ensuring safety. In the ARAMIS trial, the clopidogrel loading dose of DAPT treatment strategy (300 mg) was found to be comparable to that used in the CHANCE trial (300 mg), while differing from the dosage utilized in the POINT trial (600 mg).…”
Section: Aramis Versus Prismsmentioning
confidence: 99%